Remoção de ácido húmico em águas usando cavitação hidrodinâmica: uma abordagem experimental e computacional - CAPPA, Otávio Augusto Puglieri (2018)
Hydrodynamic cavitation emerged at the beginning of the 21st century as a promising method for supply water and wastewater treatment. So far, most studies have focused on the potential of hydrodynamic cavitation in removing pathogens and organic pollutants. The color provided by acid humic solutions is a case to be fight, mainly in the north of the country. Searches with the use of advanced oxidative process, herewith hydrodynamic cavitation, have already done. However, searches that aim the optimization of geometric parameters of hydrodynamic cavitation chambers are necessary yet. The objective of this study was assessed the color removal by a humic acid solution and optimize plates for its best efficiency. Therefore, computational simulations and experimental procedures were realized. Five different orifice plates (three with one orifice and two with multiple-orifices) were assessed. It was realized computational simulations to identify hydraulic parameters and compare them with the color remove efficiencies. In the experiment procedures were used four peroxide hydrogen volumes 30% w/v (0 ml, 1 ml, 5 ml and 10 ml) in a solution of 9 L of humic acid at 100 ppm. The oxidant use showed the optimum dye remove point with 1 ml of peroxide for 9 L of solution. The results have showed that exists two mainly plates group: plates with one orifice generates less number of lower pressure zone, high intensity and reduced pressure recovery zone; and, plates with multiple-orifices showed major number of lower pressure zone, low intensity and high-pressure recovery zone. The firsts have better efficiency of color removal with the use of oxidant agent (around 90%). While, the other group have showed significant efficiency without the use of oxidant (around 70%).